A supplement of the genus Homogryllacris Liu, 2007 (Orthoptera: Gryllacrididae: Gryllacridinae) from China - Li, Yanqing; Dou, Yujie; Shi, Fuming (Zootaxa, 2019)
In this paper, one new species of the genus Homogryllacris Liu, 2007, i.e. Homogryllacris obtusitubera sp. nov. and the previously unknown female of Homogryllacris brevispina Shi, Guo & Bian, 2012 are described from China. Meanwhile, the morphological photographs and habitus of these species are provided.